If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(b + -4) + -2 = 4(b + -6) Reorder the terms: 3(-4 + b) + -2 = 4(b + -6) (-4 * 3 + b * 3) + -2 = 4(b + -6) (-12 + 3b) + -2 = 4(b + -6) Reorder the terms: -12 + -2 + 3b = 4(b + -6) Combine like terms: -12 + -2 = -14 -14 + 3b = 4(b + -6) Reorder the terms: -14 + 3b = 4(-6 + b) -14 + 3b = (-6 * 4 + b * 4) -14 + 3b = (-24 + 4b) Solving -14 + 3b = -24 + 4b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-4b' to each side of the equation. -14 + 3b + -4b = -24 + 4b + -4b Combine like terms: 3b + -4b = -1b -14 + -1b = -24 + 4b + -4b Combine like terms: 4b + -4b = 0 -14 + -1b = -24 + 0 -14 + -1b = -24 Add '14' to each side of the equation. -14 + 14 + -1b = -24 + 14 Combine like terms: -14 + 14 = 0 0 + -1b = -24 + 14 -1b = -24 + 14 Combine like terms: -24 + 14 = -10 -1b = -10 Divide each side by '-1'. b = 10 Simplifying b = 10
| -3x+12=-5x-28 | | -(x-5)=9 | | 3p-2=-2p | | 2lnx+1=4 | | (2x+1)+2=3x+9 | | 2-4(r+6)=-2(3r+2) | | 7.1-2.6x=9.6+1.4x | | -16=-5x+4 | | 1.6h-7=4h-30 | | 3(8+7f)=5(-6-3f) | | 26x-13=13 | | 6d=d | | 371=-7(3+8x) | | 26x=2 | | -16=-8(10+b) | | 11/4w=33/5 | | 5n+4=35 | | 160=6(4n+6)+4 | | 4(2-4y)=8y+56 | | 75=3(1-4k) | | y+(-8)=8 | | 70=-5(3b-5) | | (9x+36)-(8x+1)=y | | 3-6y=-6y-3 | | 5a+18=2a | | -6(3-2x)=-90 | | (9x+36)-(8x+1)= | | 4s^2-36s+81=0 | | 8(2w+3)=4(3w-2) | | 9(4x-2)=54 | | 2(b-3)+b=3(2x-10) | | 34m+14=30m+8 |